2019
DOI: 10.1016/j.semarthrit.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Why we should definitely include intra-articular hyaluronic acid as a therapeutic option in the management of knee osteoarthritis: Results of an extensive critical literature review

Abstract: We advocate for the consideration of recommending IAHA injection as a treatment option in the management of knee OA, tailored by disease stage and patient phenotype. Future research efforts should focus on identification of OA patient subgroups that demonstrate a more robust response to IAHA, determination of long-term effects of repeat IAHA injections on patient-reported outcomes and total knee replacement-sparing effect, further elucidation of disease-modifying effects, and the potential for combination ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
97
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 91 publications
2
97
0
6
Order By: Relevance
“…HA is a high molecular weight polysaccharide that is an important part of synovial fluid and articular cartilage. Injecting HA into the knee joint cavity can physically lubricate the articular surface, reduce wear, and biologically nourish articular cartilage and promote the synthesis of endogenous HA, thereby delaying further joint disease [33][34][35]. A large number of RCTs and systematic reviews of the intra-articular injection of PRP or HA for KOA have been published [8,[36][37][38], and most studies have concluded that intra-articular injection of PRP, compared with HA, can relieve knee pain and improve the function of patients with KOA.…”
Section: Discussionmentioning
confidence: 99%
“…HA is a high molecular weight polysaccharide that is an important part of synovial fluid and articular cartilage. Injecting HA into the knee joint cavity can physically lubricate the articular surface, reduce wear, and biologically nourish articular cartilage and promote the synthesis of endogenous HA, thereby delaying further joint disease [33][34][35]. A large number of RCTs and systematic reviews of the intra-articular injection of PRP or HA for KOA have been published [8,[36][37][38], and most studies have concluded that intra-articular injection of PRP, compared with HA, can relieve knee pain and improve the function of patients with KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the in vitro ndings cannot be extrapolated to the human clinical situation, high molecular weight HA is an alternative treatment for knee OA that articular injection of HA acts to restore intraarticular lubrication, consequently improving joint biomechanics [25,26]. Recent meta-analysis also suggests that HA injections are a safe and effective alternative in treating patients with symptomatic knee OA [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, locally injected HA seems to be an effective treatment for OA comorbidity. Indeed, results from several in vitro and in vivo studies have indicated that exogenous HA can decrease the production of pro-inflammatory cytokines and stimulate the endogenous synthesis of HA and extracellular matrix components by synovial fibroblasts [5][6][7][8][9]. In all inflammatory conditions of the joint, the molecular weight of HA is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In all inflammatory conditions of the joint, the molecular weight of HA is reduced. Also, several clinical studies have shown that intra-articular HA relieves pain and improves function in symptomatic OA joints [9][10][11][12] and that the treatment has a positive global effect and is well tolerated. Some studies, mainly focused on the knee joint, have shown that repeated courses of HA treatment are safe and associated with total joint replacement delay for up to 3 years [13,14].…”
Section: Introductionmentioning
confidence: 99%